Informação a partir de regras : considerações para a solução do escândalo da dedução pela semântica inferencial-pragmática - Heck, Ralph Leal (2018)
The present study aims to examine the problem of information contained or generated in a deduction, which is known in the literature as the scandal of deduction, beginning with an exposition of some eminent theories of semantic information and proceeding with a use of certain concepts of the inferential semantics of Robert Brandom and some later elaborations of these concepts in order to shed light on the problem. Through this examination, we have concluded that it is possible to expand the information measurement framework proposed by Anderson B. de Araújo so that it is also possible to calculate the informational contribution for deductions of the rules of material inference. This conclusion is suggested when we articulate Araújo's work with the formalization proposed by Richard Evans of Brandom's authorization rules and with the AGM (Alcourrón, Gärdenfors and Makinson) paradigm of belief revision operations in the form of Horn clauses. In more detailed terms, the paper begins by presenting the precursory theory of semantic information elaborated by Carnap and Bar-Hillel, followed by the exposition of Hintikka's semantic information theory, which recognizes the problem of deduction as such and proposes a solution. Then, we present the Semantic Information Theory of D'agostino and Floridi, which suggests a different approach to solve the problem. In response to the inadequacy of these investigated proposals, some key concepts of Robert Brandom's philosophy of language are presented which serve as a sufficient philosophical framework for the exposition of an inferential-pragmatic modeling of the game of giving and asking for answers, corresponding to the fundamental scenario of exercise of language and therefore of the informative role that the deduction plays in our language practices. The modeling is based on the formalization of the inferential relations of authorization made by Evans and on the formalization of the inferential relations of commitment and their respective measurement of information developed by Araújo. It is shown that the treatment given by Evans and Araújo does not incorporate an important element for the philosophy of the language of Brandom and for the production of information by deduction, namely, the rules of material inference. To fill this gap, we use the conceptual apparatus of representation of knowledge in the form of operations on sets of beliefs, specifically for the case of rules of material inference, on sets of beliefs in the form of Horn clauses. At the end, it is proposed as main future development a calculation of measurement of information of material rules associated with the proposal of measurement of information provided by Araújo.